2013
DOI: 10.1002/jbm.a.34708
|View full text |Cite
|
Sign up to set email alerts
|

Effects of freezing/thawing on the mechanical properties of decellularized lungs

Abstract: Lung bioengineering based on decellularized organ scaffolds is a potential alternative for transplantation. Freezing/thawing, a usual procedure in organ decellularization and storage could modify the mechanical properties of the lung scaffold and reduce the performance of the bioengineered lung when subjected to the physiological inflation-deflation breathing cycles. The aim of this study was to determine the effects of repeated freezing/thawing on the mechanical properties of decellularized lungs in the physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 35 publications
(73 reference statements)
0
66
0
3
Order By: Relevance
“…The lung, however, has an additional possible route for decellularization since the media can be also infused through the trachea. In fact, both routes (trachea and pulmonary artery) alone or combined have been used to effectively decellularize lungs (Girard et al, 2013;Nonaka et al, 2014aNonaka et al, , 2014bUriarte et al, 2014;Melo et al 2014;Wagner et al, 2014aWagner et al, , 2014bKhalpey et al, 2014;Price et al, 2014). This study was focused on infusing decellularization agents through the vascular bed since is the most conventional route in lungs and the only available in other relevant organs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lung, however, has an additional possible route for decellularization since the media can be also infused through the trachea. In fact, both routes (trachea and pulmonary artery) alone or combined have been used to effectively decellularize lungs (Girard et al, 2013;Nonaka et al, 2014aNonaka et al, , 2014bUriarte et al, 2014;Melo et al 2014;Wagner et al, 2014aWagner et al, , 2014bKhalpey et al, 2014;Price et al, 2014). This study was focused on infusing decellularization agents through the vascular bed since is the most conventional route in lungs and the only available in other relevant organs.…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic (E dyn ) and static E st ) lung elastances were determined in additional organs (3 native lungs and 11 acellular lungs immediately after decellularization). To characterize the pressure-volume relationship in mechanical conditions similar to those in physiologically normal breathing, the lungs were subjected to conventional mechanical ventilation, following a procedure describe in detail elsewhere (Nonaka et al, 2014a(Nonaka et al, , 2014bUriarte et al, 2014). Briefly, the lungs were tracheally intubated, suspended vertically by gravity and placed within a chamber (32 1C and 100% humidity).…”
Section: Assessment Of Lung Elastancementioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Nonaka et al reported no significant changes in mechanical properties of decellularized lungs after several freeze/thaw cycles 23 . Both decellularization and freezing/thawing resulted in a decrease in stiffness, but the two processes…”
Section: Compression Testmentioning
confidence: 97%
“…The rapid thermal change brought on by repeated freezing and thawing results in an osmotic response and the formation of intracellular ice crystals, which accelerate cell lysis within the liver [Lu et al, 2011]. Even though some concerns have been raised regarding the changes in the viscoelastic properties of these tissues [Chan and Titze, 2003], studies have proven that the freeze-thaw process used for decellularization and storage induces only minor differences in the mechanical properties of the ECM compared to other methods [Nonaka et al, 2014], and can therefore be used if both temperature and time are carefully controlled.…”
Section: Decellularization Techniquesmentioning
confidence: 99%